Discovering the best practices of Total Quality Management influencing performance in the Moroccan hospitality industry - Ikram Bel Haddioui (European Scientific Journal, ESJ, 2025)
This study aims to investigate the relationship between Total Quality Management and hotel performance, with a particular focus on identifying best practices from the European Foundation for Quality Management that could contribute to enhancing business results within the hospitality sector. A quantitative confirmatory study was conducted using a five-point Likert scale questionnaire, administered to 93 Moroccan hotels, targeting senior managers with a quality management background. The Partial Least Squares Structural Equation Modeling (PLS-SEM) technique was used to analyze the collected data. The findings indicate that Total Quality Management is a driver of both financial and customer performance. Similarly, strategy and processes are the most important enablers in fostering hotel performance. This research offers a distinctive empirical contribution by examining how Moroccan hotels embrace a significant managerial approach to enhance their performance. Furthermore, the study focuses on a widely recognized model for business excellence, providing a targeted and in-depth analysis of how specific practices within this framework can impact hotel performance.